Vampire Bat Salivary Plasminogen Activator Promotes Robust Lysis of Plasma Clots in a Plasma Milieu Without Causing Fluid Phase Plasminogen Activation - Hare, Timothy R; Gardell, Stephen J (Thrombosis and Haemostasis, 1992)
Vampire bat salivary plasminogen activator (BatPA), human tissue-type plasminogen activator (tPA) or streptokinase (SK) were incubated in human citrated plasma containing a plasma clot that was radiolabelled with iodine-125 fibrin(ogen). Complete clot dissolution by BatPA (30 nM) was associated with slight activation of “fluid phase” plasminogen; the plasma levels of functional fibrinogen and α2-antiplasmin decreased by only 8 and 19%, respectively. Addition of SK (3,600 IU/ml) to the clot-containing plasma caused complete clot lysis and massive activation of the “fluid phase” plasminogen, leading to >60 and 96% decreases of the functional levels of fibrinogen and α2-antiplasmin, respectively. Incubation of tPA (30 nM) in clot-containing plasma caused complete clot lysis as well as substantial activation of “fluid phase” plasminogen; the plasma levels of functional fibrinogen and α2-antiplasmin decreased by 45 and 79%, respectively. The profound degradation of fibrinogen in the SK and tPA but not BatPA-containing samples was confirmed by immunoblot analysis. Additional experiments showed that the presence of soluble clot lysate in plasma containing tPA enhanced the extent of fibrinogen degradation from 25% to >60%; the addition of soluble clot lysate to the plasma containing BatPA did not prompt further fibrinogen degradation. Finally, studies using exogenous α2-antiplasmin suggested that plasmin generated via tPA-mediated activation of “fluid phase” plasminogen does not play an important role in clot dissolution.